Neighborhood effects on crime and youth violence: the role of business improvement districts in Los Angeles - Macdonald, John (Technical report, 2009)
Theoretical explanations for youth violence at the community level -- Budgetary and organizational characteristics of bids -- Observations of business improvement districts -- Family, individual, and community effects on youth violence -- Analysis of bid effects on reported violent crime -- Summary and conclusions